The Naval War in South African Waters, 1939-1945 - Kleynhans, Evert (African Sun Media, 2022)
The Naval War in South African Waters, 1939-1945 provides a critical reappraisal of the naval war waged in South African waters during the Second World War. The book investigates this broad topic by focussing on several interrelated aspects such as: the wartime strategic importance of South African waters; the rival Axis and Allied naval strategies in the southern oceans; the development of the South African coastal defence system; the full extent of the Axis naval operations in the southern oceans; the naval intelligence war; and, finally, the antisubmarine war waged in South African waters. Based on extensive archival research in South Africa and the United Kingdom, and supplemented by a wealth of secondary material, the book introduces a fresh, in-depth discussion on a largely forgotten episode of South African military history.